PENGARUH REALISASI ANGGARAN BELANJA PEGAWAI, BELANJA BARANG DAN BELANJA MODAL TERHADAP PENETAPAN PAGU INDIKATIF DI LINGKUNGAN KEMENTERIAN AGAMA KABUPATEN BANGGAI - Winter, Juwita Sari (Katalogis, 2017)
The study intends to determine and analyze: 1) the realization of personnel expenditure budget, goods expenditure, capital expenditure and indicative budget preparation; 2) the significant impact of realization of personnel expenditure budget, goods expenditure and capital expenditure on determining indicative budget; 3) the significant impact of the realization of personnel expenditure budget on indicative budget preparation; 4) the significant impact of the realization of goods expenditure budget on indicative budget preparation; 5) the significant impact of the realization of capital expenditure budget on indicative budget preparation. The study applies multiple linear regressions analysis with SPSS 17.0. Population consists of working units in The Ministry of Religion and sample is determined by purposive sampling method. The result indicates that: 1) realization of personnel expenditure budget, goods expenditure and capital expenditure have significant impacts on indicative budget preparation; 2) personnel expenditure budget realization has significant impact on indicative budget preparation; 3) goods expenditure realization has significant impact on indicative budget preparation; 4) capital expenditure realization has significant impact on indicative budget preparation.